Dual Band Circular Polarized Design of Rectangular Microstrip Antenna For GPS L-band and Galileo E-band Applications - Deshmukh, Amit A.; Page, Tejal P.; Chavali, Venkata A. P. (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
Design of rectangular microstrip antenna employing three rectangular slots of unequal lengths on one of the patch edges, is presented to achieve dual band and dual sense circular polarized characteristics. Circular polarized response in the two bands is attributed to the optimum inter-spacing in between the rectangular patch’s TM10, TM11 and TM12 resonant modes. For axial ratio less than 3 dB, an optimum design offers axial ratio bandwidth of 26 MHz (2.05%) and 73 MHz (4.59%) in the dual bands, bearing frequency ratio of 1.25. This circular polarized bandwidth lies inside the VSWR < 2 bandwidth of 665 MHz (49.83%). Antenna offers radiation pattern maximum in the broadside direction across axial ratio and VSWR bandwidth, with a gain of more than 6 dBic. For the obtained antenna characteristics, the three rectangular slot cut design is suitable in variety of applications like, GPS L1 & L2 bands, and Galileo E1 & E6 bands. The experimental verification has been carried out for the proposed configuration that shows close agreement against the simulated results.